A Lived Experience of a University Retired English Teacher: A Narrative Inquiry - Timsina, Jib Nath (Researcher: A Research Journal of Culture and Society, 2021)
Teaching is a challenging job. It requires mentoring and helping students to grasp the meaning and understand the message the subject delivers. A teacher is one who inspires guides, enlightens and motivates the learner. It is lifelong process. This article is based on narrative inquiry research on the lived experience of a recently retired English teacher from Tribhuvan University who contributed a lot in English education. It explores how a master degree holder in English education joined at university and constructed and reconstructed his identity in his teaching profession unless he retired. Data were collected from face to face in depth interviews and telephone conversation then analyzed through narrative case analysis. The findings show that a university English teacher develops and modifies his identity through engaging himself in different professional development activities, interacting with different socializing factors and experiencing various emotions in university activities. He also works as curriculum developer, examiner, and invigilator, external and internal examiner in practical examinations. He has to labour hard in his whole professional period and has to balance his emotional behaviours, that is, happy moments as well as frustrated moments. The paper concludes with some implications for language teachers in context of education campuses under faculty of education in T.U.